2015
DOI: 10.5539/ijef.v7n12p168
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Long-Run Fisher Effect in Selected African Countries: Evidence from ARDL Bounds Test

Abstract: This paper tests the validity of the Fisher hypothesis for a sample of ten African countries. Recognizing the possibility of spurious regression results, we undertook unit root and cointegration tests. We found nominal interest rates to be I(1) series while inflation rates are I(0) series. Hence, we employed the bounds test to cointegration. The results provide evidence supporting the full Fisher effect only in Kenya. In Cote d'Ivoire and Gabon, we found a positive but less than one-for-one reaction of nominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The results show the existence of the partial Fisher effect. The findings support those reported, for example, by Huizinga and Mishkin ( 1986 ), Kandel et al ( 1996 ), Lee ( 2009 ), Awomuse and Alimi ( 2012 ), and Yaya ( 2015 ), while deviating from those of Panopoulou and Pantelidis ( 2016 ) for Ireland and for Switzerland (Paleologos and Georgantelis 1996). Similar findings have been reported for Malaysia, Thailand, South Korea, Philippines, and India as well (Phiri and Said 2001; Abubakar and Sivagnanam 2017 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results show the existence of the partial Fisher effect. The findings support those reported, for example, by Huizinga and Mishkin ( 1986 ), Kandel et al ( 1996 ), Lee ( 2009 ), Awomuse and Alimi ( 2012 ), and Yaya ( 2015 ), while deviating from those of Panopoulou and Pantelidis ( 2016 ) for Ireland and for Switzerland (Paleologos and Georgantelis 1996). Similar findings have been reported for Malaysia, Thailand, South Korea, Philippines, and India as well (Phiri and Said 2001; Abubakar and Sivagnanam 2017 ).…”
Section: Resultssupporting
confidence: 88%
“…Their findings show that the full Fisher effect is supported by all countries in the sample except Ireland and Switzerland. With respect to the African economies, Yaya ( 2015 ) employed the ARDL bounds test cointegration technique to examine the validity of the Fisher effect for 10 African countries. He reported that the full Fisher effect holds for Kenya, while Cote d’Ivoire and Gabon have the partial Fisher effect.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Controlling inflation with the help of interest rates has become the only goal of many Central Banks during the previous few decades [26] because inflation targeting is a complete monetary framework that ensures price stability along with other monetary objectives [27][28][29]. However, inflationary pressures can lead to contractionary monetary policy that impacts economic growth, poverty, and inequality [30][31][32][33]. Thus, the direction of causality between inflation and interest rate is the prime concern because it is related to the potency of the monetary policy framework.…”
Section: Empirical Debatementioning
confidence: 99%
“…Adegboyega et al (2013) tested the Fisher effect with the aautoregressive distributed lag (ARDL) model and found partial effect for Nigeria. Yaya (2015) used the co-integration technique for ten African countries and found the Fisher effect only for Kenya. Cai (2018), using the quantile cointegration technique, found the Fisher effect for the US.…”
Section: Literature Reviewmentioning
confidence: 99%